An Evaluation of Cytotoxicity of Iron Oxide Nanoparticles with Hydrogen Peroxide Endodontic Irrigant - Saraa N. Al-Malla; Ali M. Al-Naimi (University of Mosul, College of Dentistry, 2023)
Aims: The aim of this research was to determine the cytotoxic effect of different concentrations of iron oxide nanoparticles (IONPs) in combination with hydrogen peroxide (H2O2) in vitro as a potential endodontic irrigating solution. Materials and Methods: Cytotoxicity of IONPs at concentrations (8, 4, 2, 1, 0.5, and 0.25 mg/ml) with 3% H2O2 were evaluated on cultured Human Dermal Fibroblast (HDFn) cell lines. Cytotoxicity was assessed after 10 minutes of exposure using Mossman's Tetrazolium Toxicity (MTT) assay. Results: Tukey's test indicated that no significant difference in cell viability was found at lower concentrations (0.2, 0.5, 1, and 2 mg/ml). While at a concentration of 4 and 8 mg/ml, the cell viability was not significantly different from each other whereas, significantly different from previous concentrations. Conclusion: From the gained data, it can be deduced that IONPs+H2O2 had almost no cytotoxic effect on HDFn cell viability at concentrations 0.2, 0.5, 1, and 2 mg/ml, while a moderate decrease of survival has been observed at concentrations 4 and 8 mg/ml.